Measures for climate change adaptation in agriculture. Opportunities for climate action in agricultural systems - Vermeulen, Sonja J.; Dinesh, Dhanush (2016)
In this info note we provide a brief overview of key adaptation measures in agriculture drawing on research for development efforts by CGIAR Centres and partners, taking into account the diversity of agricultural systems, the role of indigenous knowledge, differences in scales of adoption, and potential cobenefits of these measures. A twinned info note considers agricultural practices and technologies, which are one sub-set of adaptation measures.